Collective identity and integration policy in Denmark and Sweden - Geugjes, Marilena (Springer Fachmedien Wiesbaden, 2021)
Introduction -- Danishness and Swedishness in Academic Discourse -- Identity and Integration -- Methodology -- (Re-)Constructing Danishness and Swedishness -- Collective Identity and Integration Policy -- Conclusion.
Keywords: Hochschulschrift; Vergleichende politische Wissenschaft; Dänemark; Schweden; Identität; Integration